Dome A Wind Turbine ... - Gerges, Matthew (UNSW Sydney, 2025)
No mid-range power (5–50 kW) commercial wind turbine suitable for inland Antarctic weather currently exists. This project documents the design of the Dome A Wind Turbine (DAWT), a 10 kW wind turbine optimised for Dome A, one of the coldest and least windy places on Earth. The overall design of the turbine was determined through analysis of other Antarctic projects and wind turbines. The design of the tower, foundation and blades were determined and then optimised through engineering standards and simulation. All of DAWT’s designed components are unique to its environment and constraints; the foundation is particularly novel as it minimises shipping weight by procuring materials in situ for construction. A series of bearing lubricants were experimentally tested at low temperatures following ASTM D1478-20 to determine the best lubricant for DAWT. ...